Effect of Probiotic Supplementation in Formulated Feed on Growth of Tambaqui (Colossoma macropomum)Fingerling - Afdola, Afdola; Suharman, Indra; Adelina, Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAK The research was conducted for 56 days from December 2016 to February 2017. The aim of this research was to determine effect of probiotic supplementation in formulated feed on growth and feed utilization of Tambaqui (Colossoma macropomum). This study uses a completely randomized design (CRD) with one factor, four level treatments and three replications. This fish used in this research with average initial weight of 0.73 g. Fish were reared in 100x100x100 (cm3) cages with the stocking density of 25 fish/cage. The treatment given was different concentration of probiotic in feed, consisting of : P0 (without probiotic supplementation), P1 (5 ml/kg feed), P2 (10 ml/kg feed) and P3 (15 ml/kg feed). The result show that probiotic supplementation in  formulated feed did not give a significant effect (P>0,05) on the growth and feed efficiency, butt have a significant effect (P>0,05) on protein retention. The study show that probiotic supplementation of 15 ml/kg feed gave best growth and feed peformance of Tambaqui (Colossoma macropomum). Key word : Colossoma macropomum, feed, growth, probiotic, Tambaqui